THE ROLE OF ACCOUNTING INFORMATION SYSTEMS IN THE UTILIZATION OF TECHNOLOGY FOR DIGITAL BOOKKEEPING IN SMES - Tigha Anaku Putri; Angellina Merry Susetyawan; Sekararum Sherlenadya Purba; Hatkasum Ratu Mony; Zara Tania Rahmadi; Muhammad Aria Wahyudi; Dias Adhi Dharma (Bridging Journal of Islamic Digital Economics and Management, 2024)
The purpose of writing this article is to identify the use of technology, especially in the field of accounting, understand the role of accounting information systems in micro, small and medium enterprises (MSMEs), and the application of digital bookkeeping in MSMEs. The approach carried out is a case study approach using relevant journals. The results obtained show that currently small and medium-sized enterprises (MSMEs) have digitized their activities using technology. For example, in terms of sales and payments. However, many MSME bookkeepers still use paper to record books manually. The purpose of coaching is with the hope that currently with the rapid development of science and technology, small and medium enterprises can effectively and efficiently carry out accounting in their business and build technology-based small and medium enterprises (MSMEs).